A novel and durable photochromic cotton-based fabric prepared via thiol-ene click chemistry. (December 2019) - Bao, Bingwei; Bai, Shuoao; Fan, Ji; Su, Jiahua; Wang, Wei; Yu, Dan
Abstract: Photochromic materials have drawn increasing researchers' attention due to their excellent reversible discoloration and brilliant physical properties. In this paper, we proposed a novel method of preparing photochromic and thermochromic cotton fabric via thiol-ene click chemistry to establish chemical bonds between spiropyrane derivatives and thiol-modified cotton. The synthesized photochromic materials were characterized by FTIR, 1 H NMR and ultraviolet (UV), and the as-prepared fabrics were featured by FTIR and Raman spectra as well as SEM. The results indicated that the photochromic materials have been successfully synthesized and the resultant cotton fabric possesses brilliant and durable photochromic properties, including noticeable and quick color alteration under UV radiation and under heating. Furthermore, the appropriate fatigue resistance and durable washing fastness ensure it a good candidate in the fields of photochromic and thermochromic textile materials. Graphical abstract: Image 1 Highlights: Spiropyrane photochromic fabric was proposed. The fabric presents brilliant reversible color changing ability. The application performance of as-prepared fabric are outstanding.